Investigation of tin and antimony based anodes with enhanced cycle life for sodium-ion batteries - Edison, Eldho (Nanyang Technological University, 2020)
Sodium-ion batteries (SIBs) are proposed as a low-cost alternative to the existing lithium-ion batteries (LIBs) in view of the abundance and wide distribution of the sodium reserves. To realize the practical deployment of the SIBs, however, it is crucial to develop high capacity sodium-storage materials. In this thesis, Sn and Sb based materials have been explored considering their high capacity, low cost, environmental benignity and safety aspects. Various scalable, high-throughput and industrially viable synthetic methodologies including melt-spinning and high-energy ball milling techniques have been employed to synthesize the active materials. The sodium-storage mechanism, structural and morphological evolution and transformations in the active materials were probed. The various strategies adopted in the study could significantly improve the cycle life of the anodes, which is considered as the Achilles’ heel of alloying and conversion anodes. Additionally, preliminary full-cell investigations were carried out to gauge the practical implications and utility of the synthesized anode materials for sodium-ion batteries. Various novel synthetic methodologies and scientific and technological findings aiding high energy density sodium-ion batteries based on alloying and conversion anodes were achieved. The novel insights from the study as well as the proposed future works could guide and spawn further research and technological advancements towards the practical deployment of SIBs.